2009
DOI: 10.1161/hypertensionaha.109.140350
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Correlates With Lenticulostriate Arteries Visualized by 7T Magnetic Resonance Angiography

Abstract: Abstract-Hypertension, a major risk factor for stroke, is associated with altered arterial anatomy and function; however, the limited resolution of current imaging techniques has restricted the in vivo study of microvascular changes in the brain. In this report, we quantitatively examined the lenticulostriate arteries in hypertensive patients using ultrahigh-field 7T MRI. We compared the number of stems and branches, curvature, and tortuosity of the lenticulostriate arteries by 3D time-of-flight magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
(31 reference statements)
2
64
1
2
Order By: Relevance
“…7,8 Lacunar infarcts account for Ͼ20% of all strokes, and the basal ganglia are involved in 35%-44% of intracerebral hemorrhages. 9,10 Thus, in vivo imaging of LSAs could provide important insights for understanding the pathophysiology and mechanism of microvascular diseases associated with hypertension.…”
mentioning
confidence: 99%
“…7,8 Lacunar infarcts account for Ͼ20% of all strokes, and the basal ganglia are involved in 35%-44% of intracerebral hemorrhages. 9,10 Thus, in vivo imaging of LSAs could provide important insights for understanding the pathophysiology and mechanism of microvascular diseases associated with hypertension.…”
mentioning
confidence: 99%
“…In an imaging study of the LSA by TOF-MRA using a 7 T MR image, there was a significant difference in LSA visualisation between subjects with and without hypertension at age 45 years or under [10]. The others found no such difference in subjects more than 45 years old.…”
Section: Discussionmentioning
confidence: 94%
“…LSA branches have been successfully visualised with a 7-T MRI scanner by using TOF [8,9], and the relationship between decreased LSA visualisation and hypertension has also been demonstrated [10]. However, availability of a 7-T MRI system is very limited, and it is currently used for research purposes only.…”
mentioning
confidence: 99%
“…To capture the total cSVD-related brain damage, a total SVD score was proposed, which integrates all individual MRI markers into one measure. 50 Cross-sectional studies have shown that this total SVD score is associated with higher blood pressure levels, 51 hypertension, age, other risk factors for SVD 50 and lower cognitive performance. 52,53 This SVD score has never been applied in longitudinal cognition research.…”
Section: Csvd and Cognitive Functionmentioning
confidence: 99%
“…48 In addition, with 7T MR angiography it might be possible to visualize small vessels without using contrast agents. [49][50][51] Besides a more detailed visualization of structural changes, 7T MRI might also enable the opportunity to show functional changes, such as blood flow velocity and pulsatility in the small vessels. 52 Although 7T MRI is unlikely to replace 3T MRI in clinical practice, the use of 7T MRI in research offers more information on hypertensive brain damage, both at a structural and a functional level.…”
mentioning
confidence: 99%